STUDI PARTISIPASI PERKUMPULAN MASYARAKAT SURAKARTA (PMS) DALAM MENDUKUNG INTEGRASI SOSIAL DI KOTA SURAKARTA - Rahman, Rifqi Kurnia; Gunawati, Dewi; Yuliandari, Erna (Educitizen, 2018)
ABSTRACTThe purpose of this study is: 1) To ascertain the participation of Perkumpulan Masyarakat Surakarta (PMS) in supporting the social integration in Surakarta City; 2) To ascertain the obstacles faced by Perkumpulan Masyarakat Surakarta (PMS) in supporting the social integration.This study used a qualitative research approach; the type of this research was described qualitatively. The data source obtained from the informants, places, events, and document. The sampling technique used purposive sampling. The data collection technique by the interview, observation, and document analysis. The validity data used triangulation data and triangulation methods. The data analysis used interactive analysis model. Based on the result of this study, it can be concluded that (1) the participation of Perkumpulan Masyarakat Surakarta (PMS) in supporting the social integration in Surakarta City as follows: a) The alteration of the name and structure organization as the beginning of the social integration process; b) The communication and interaction of the members in activities of Perkumpulan Masyarakat Surakarta (PMS) as the foundation of the strengthening of the social integration. The obstacles faced by Perkumpulan Masyarakat Surakarta (PMS) in supporting the social integration in Surakarta City, as follows: Internal Factor: (1) The managers of Perkumpulan Masyarakat Surakarta (PMS) have their own business, so that they can not fully focus on the activities of organization; (2) The lack of discipline of the members in following various organization that they follow. b) External factor: (1) The perceptions of the community still believing that Perkumpulan Masyarakat Surakarta (PMS) is an organization of Chinese descent. KeyWord: Participation, Perkumpulan Masrakat Surakarta (PMS), Social                Integration.